A STUDY ON EVACUATION SIMULATION FOR GUIDING TOURISTS IN HIMEJI CASTLE BASED ON A SURVEY OF TOURISTS’ INTENTIONS IN EVACUATION AFTER EARTHQUAKE - Sakai, Kohei; Honda, Ayaka; Mongkonkerd, Siriluk; Perera, Sachi; Cui, Mingji; Toyoda, Yusuke; Taniguchi, Hitoshi; Kanegae, Hidehiko (ASEAN Journal on Hospitality and Tourism, 2014)
Many tourists tend to visit historic areas. Nevertheless, their knowledge about these areas, disaster prevention, and evacuation is not sufficient. Japan has met with several large-scale disasters, namely the Great East Japan Earthquake in 2011, the Great Hanshin-Awaji Earthquake in 1995, and will potentially face the Nankai Trough Quake in the future.This paper, based on a survey of tourists’ intentions in evacuation after an earthquake in Himeji castle, shows an evacuation simulation and the measures for supporting tourists’ evacuation. Himeji Castle, the area investigated by this study, is one of the world heritage sites in Japan.First, this study revealed decision-making rules and used these to categorize tourists. This paper investigated the sources of information that tourists consider before starting evacuation. According to the results of the questionnaire survey, four groups were categorized by analytic hierarchy process and cluster analysis. As a result, many tourists set a high value on information from sign boards and staff of the Himeji castle before starting evacuation. Next, in a similar manner, using analytic hierarchy process, this survey found that many tourists consider information from signboard and staff when choosing evacuation routes, and the respondents were categorized into four groups using cluster analysis.Second, this study developed an evacuation simulation taking into account the tourists’ intentions about evacuation. This study used SOARS, Spot Oriented Agent Role Simulator, as a simulation platform and adopted a Spot-Link type model. Third, this study simulated six cases that have different evacuee flows near “Bizen-gate” and routes in sightseeing, and evaluated them by transition of the number of evacuees who were able to reach an evacuation area and the number of evacuees who could not move because of bottlenecks. As a result, we found two effective measures for guiding tourists.